Results of single-stage two-stage reconstructive surgeries in young women with breast cancer - A. Kh. Ismagilov; V. E. Karasev (Опухоли женской репродуктивной системы)
The leading position among cancer in women is breast cancer. The work analyzed the results of surgical treatment of 274 women aged 18 to 40 years with various stages of breast malignancy who underwent only a radical mastectomy (n = 141, group I), or a radical mastectomy with a single two-stage mammoplasty (n = 133, group II). The comparison group (n = 40, group III) was composed of healthy women after breast reconstruction based on aesthetic indications. When performing a mastectomy with subsequent one-time reconstruction, 68.4 % of cases achieved an excellent result, in 26.6 % of cases – good, in 4.5 % of cases – satisfactory, in 1.5 % – unsatisfactory. In women of group I, relapses of the disease developed 57.8 % more often, and metastasis – 1.9 times often, than in patients of group II. It was established that one-time reconstruction of the breast has a beneficial effect on the psycho-emotional state of women suffering from breast cancer, without increasing the risk of developing a relapse of the disease. The application of a two-stage technique of breast repair using tissue expanders in most cases allows achieving excellent cosmetic results.